Just add water: Prisons, therapeutic landscapes and healthy blue space - Jewkes, Yvonne (Criminology & criminal justice, 2020)
‘Healthy prisons’ is a well-established concept in criminology and prison studies. As a guiding principle to prisoners’ quality of life, it goes back to the 18th century when prison reformer John Howard regarded the improvement of ventilation and hygiene as being essential in the quest for religious penitence and moral reform. In more recent, times, the notion of the ‘healthy prison’ has been more commonly associated with that which is ‘just’ and ‘decent’, rather than what is healthy in a medical or therapeutic sense. This article interrogates the ‘healthy prison’ more literally. Drawing on data gathered from a UK prison located on a seashore, our aim is to explore prisoners’ rational and visceral responses to water in a setting where the very nature of enforced residence can have negative effects on mental health. In expanding the possibilities for the theorization of the health benefits that waterscapes may generate, and moving the discussion from healthy ‘green space’ to healthy ‘blue space’, the article reveals some of the less well-known and under-researched interconnections between therapeutic and carceral geographies, and criminological studies of imprisonment.